2019
DOI: 10.1038/s41598-019-46824-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of KEAP1/NRF2/P62 signaling alleviates high phosphate-induced calcification of vascular smooth muscle cells by suppressing reactive oxygen species production

Abstract: Vascular calcification is a complication of diseases and conditions such as chronic kidney disease, diabetes, and aging. Previous studies have demonstrated that high concentrations of inorganic phosphate (Pi) can induce oxidative stress and vascular smooth muscle cell calcification. KEAP1 (Kelch-like ECH-associated protein 1)/NF-E2-related factor 2 (NRF2) signaling has been shown to play important roles in protecting cells from oxidative stress. The current study aims to investigate the possible involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 61 publications
1
54
0
2
Order By: Relevance
“…Recent data have also validated that kelch like ECH associated protein 1 (KEAP1) is an inverse regulator of the antioxidant response transcription factor NRF2 (Best et al, 2019), whereas KEAP1 can also serve as a direct substrate of OGT (Chen et al, 2017b). The KEAP1/NRF2 axis can mediate responses of VSMCs to oxidative stress in high phosphate-induced calcification, and specifically, small interfering RNA (siRNA)-mediated knockdown of NRF2 and P62 can augment levels of reactive oxygen species and calcium deposition in VSMCs (Wei et al, 2019). Based on previous evidence, we hypothesized that OGT participates in the pathogenesis and process of high phosphate-induced VC in CKD settings, which may be involved in the regulation of the KEAP1/NRF2 axis.…”
Section: Introductionmentioning
confidence: 85%
“…Recent data have also validated that kelch like ECH associated protein 1 (KEAP1) is an inverse regulator of the antioxidant response transcription factor NRF2 (Best et al, 2019), whereas KEAP1 can also serve as a direct substrate of OGT (Chen et al, 2017b). The KEAP1/NRF2 axis can mediate responses of VSMCs to oxidative stress in high phosphate-induced calcification, and specifically, small interfering RNA (siRNA)-mediated knockdown of NRF2 and P62 can augment levels of reactive oxygen species and calcium deposition in VSMCs (Wei et al, 2019). Based on previous evidence, we hypothesized that OGT participates in the pathogenesis and process of high phosphate-induced VC in CKD settings, which may be involved in the regulation of the KEAP1/NRF2 axis.…”
Section: Introductionmentioning
confidence: 85%
“…Sequestosome-1, an endogenous signaling molecule, activates the Nrf2 pathway via non-canonical mechanisms by blocking Nrf2 binding to Keap1 [ 88 ] ( Table 1 ). Sequestosome 1, also called p62, not only competes with Nrf2 to bind to Keap1 and block the formation of Nrf2–Keap1 complex, but also promotes the autophagic degradation of Keap1 [ 48 , 88 ]. For example, Nrf2 silencing downregulates p62 expression while upregulating Keap1 expression at the mRNA and protein levels in vascular smooth muscle cells.…”
Section: Role Of the Nrf2/are Pathway In Cancer Chemopreventionmentioning
confidence: 99%
“…For example, Nrf2 silencing downregulates p62 expression while upregulating Keap1 expression at the mRNA and protein levels in vascular smooth muscle cells. Conversely, p62 silencing dramatically upregulates Keap1 and downregulates Nrf2 at the mRNA and protein levels, suggesting p62 may be effective in downregulating Keap1 protein via autophageal degradation [ 88 ].…”
Section: Role Of the Nrf2/are Pathway In Cancer Chemopreventionmentioning
confidence: 99%
“…This effect is attributed to the activation of the Nrf2-ARE signaling pathway, leading to the induction of autophagy in VSMCs [ 197 ]. Additionally, Wei et al found that silencing of Nrf2 increases VSMC calcification through elevated ROS production [ 198 ].…”
Section: Controlling Ros Production As a Therapeutic Approach To Pmentioning
confidence: 99%